Hubungan Persepsi Iklim Kerja dengan Motivasi Kerja Karyawan PT Aneka Gas Industri Tbk Bekasi - Nur Bainah Ellen; Sariah Sariah (Jurnal Persada Husada Indonesia, 2021)
The work climate of an organization is a characteristic that distinguishes one organization from another and affects the people in the organization. Employee work motivation is an impulse that arises from the individual (internal) and from outside the individual (external) which causes employees to be willing and willing to direct their abilities in completing their responsibilities, so that the goals of employees and the company can be achieved by showing the characteristics of mature employees. This study aims to determine the relationship between perceptions of work climate with work motivation of employees of PT. Aneka Gas Industri Tbk Bekasi. The design of this research is quantitative with a cross sectional approach. The dependent variable is work motivation with the independent variables are the characteristics of the respondents and environmental factors. The study was conducted at PT Aneka Gas Industri Tbk – Bekasi from March to August 2020. The population in this study was 118 employees. Sampling with accident sampling technique using the Slovin formula, obtained 68 respondents as a sample. Data collection by questionnaire and document review. Descriptive univariate data analysis and bivariate analysis used Chi Square with 95% confidence interval and value: 0.05. The majority of respondents are 40 years old, male, high school education level, and marital status are married. Most of the employees worked as operators and staff, with the most tenure of 16 years. According to respondents, the room temperature is comfortable, but the humidity is not comfortable. Likewise, heat radiation is less comfortable, dust is also less comfortable, and metal vapor is less comfortable. Most employees work motivation in the high category. The results of the bivariate analysis showed that the eleven independent variables analyzed contained two significant variables, namely room temperature (p=0.017), and humidity (p=0.007) which were significantly related to work motivation.